Permainan Uno Stacko: Upaya Meningkatkan Kemampuan Mengenal Nilai Tempat Bagi Anak Berkesulitan Belajar Kelas III SD N 22 Payakumbuh - Utami, Atika Yanbi; Kasiyati, Kasiyati (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
This research is motivated by the problem of children having learning difficulties in the academic field that is about the value of place units, tens, and hundreds. The researchers found problems at SD N 22 Payakumbuh. The subjects of this study were children who had difficulty learning female sex who were sitting in class III. The purpose of this study is to improve the ability to recognize the value of places through the UNO Stacko game for children with learning difficulties. This study uses the Single Subject Research (SSR) method with A-B-A design. To measure and collect data in baseline I (A1) conditions until stable data is conducted for five meetings. Furthermore, providing intervention conditions (B) through the Stacko UNO game is conducted for eight meetings until the data is stable. Provide baseline conditions II (A2) for three meetings that aim to see if there is an influence of the intervention given to the child. The results of this study are the Stacko UNO game can improve children's ability to recognize place values that can be proven by overlapping percentages, ie baseline I (A1): intervention (B) is 0% and intervention (B): baseline II (A2) 37.5% . From these data it can be concluded that the Stacko UNO game is effective in increasing the ability to recognize the value of places where children have difficulty learning.